Educating and Socializing the Use of Flashcards to Optimize Mental Health Literacy Among Teenagers: Edukasi dan Sosialisasi Penggunaan Flashcards untuk Mengoptimalkan Literasi Kesehatan Mental di Kalangan Remaja - Daulay, Wardiyah; Lailan Nasution, Mahnum (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Education is very necessary to increase mental health literacy among teenagers. Education using flash cards as a medium for socialization is an interesting way. It is hoped that the knowledge and skills provided through simple and interesting media will be able to increase adolescent literacy regarding adolescent mental health. With the right service method, flashcards can be accessed by more teenagers and provide significant benefits for increasing mental health literacy. This service activity is carried out as an implementation of the tridharma of higher education which involves a service team and involves students in its implementation. So this activity can also be used to support the main performance indicators of higher education, especially involving lecturers and students outside the campus. The methods used in this service activity are FGD, lectures, discussions, demonstrations and practice with teenagers and teachers. The results of the community service that had been carried out were that before the education was carried out, the majority were in the fair category, 44 people (73.4%), and after the education and socialization of mental health literacy flashcards for teenagers, the majority were in the good category, namely 30 people (50%).. It can be seen from the increase in average literacy before and after being given education with a difference in mean literacy of 6.917. It is hoped that the use of these flash cards will continue to be provided by the school on an ongoing basis to be able to monitor the mental health status of teenagers.